Scientific Data Path of the Particle Telescope Onboard the FORESAIL-1 Satellite - Salomaa, Lassi (My University, 2019)
Field Programmable Gate Arrays (FPGAs) are compelling for use in satellites, which do not have high budgets. Radiation can however cause errors in FPGAs and this has to be taken into account in the design process. FPGAs can be made with different technologies, and these technologies have different sensitivities to radiation. Nowadays Flash-based FPGAs start to be as good, or better than traditionally used antifuse technology, when radiation hardening is implemented during the design process. Flash technology also has other strengths when comparing to antifuse technology. For example, they can be reconfigured several times. Particle Telescope (PATE) is a payload of the FORESAIL-1 satellite. The FPGA used in the PATE instrument is Microsemi ProASIC3EL A3PE3000L, which is Flash switch based. The FPGA is used for implementing the scientific data paths, which include pulse filtering, pulse height analysis and particle classification. FPGA is also responsible for communication to the satellites On-Board Computer (OBC), housekeeping and other tasks. Radiation can cause errors in FPGA configuration memory and also in the user data. These errors, known as bit-flips, can cause configuration changes and even permanent damage. Design techniques to mitigate these errors include Triple Modular Redundancy (TMR), guard gate filtering, safe Finite State Machine (FSM) coding, scrubbing, and other various techniques. In this thesis, these methods are presented and taken into account while developing the design for the data path. This thesis demonstrates how to develop a design for Flash-based FPGA that is launched to Low Earth Orbit (LEO). The developed design is the scientific data path for particle detection and particle energy determination. The data path was developed for PATE and it was tested with simulators and in laboratory.

Kenttäohjelmoitavat porttipiirit (FPGA) soveltuvat hyvin satelliitteihin, joiden kehitykseen ei ole käytettävissä suurta budjettia. Suunnitteluprosessissa on kuitenkin otettava huomioon se, että säteily voi aiheuttaa virheitä FPGA piireissä. FPGA kyetään toteuttamaan käyttäen erilaisia teknologioita ja näillä teknologioilla on eri herkkyys säteilyyn. Nykyään Flash-pohjaiset FPGA:t ovat yhtä kestäviä, tai kestävämpiä kuin perinteisesti käytetyt antifuse teknologiat, kun kehitysvaiheessa implementoidaan säteilynsuojaus. Tämän lisäksi Flash teknologialla on myös muita etuja verrattaessa antifuse teknologiaan. Esimerkkinä mahdollisuus uudelleenkonfigurointiin. Hiukkasteleskooppi (PATE) on FORESAIL-1 satelliitin hyötykuorma. PATE instrumentissa käytetty FPGA on ProASIC3EL A3PE3000L ja se on Flash pohjainen. FPGA:ta käytetään tieteellisen datapolun toteuttamiseen, joka sisältää pulssin suodatuksen, pulssin korkeusanalyysin ja hiukkasten luokittelun. FPGA on vastuussa myös kommunikoinnista satelliitin päätietokoneelle (OBC), housekeeping datan keräyksestä ja muista instrumentille tarpeellisista operaatioista. Säteily voi aiheuttaa virheitä FPGA:n konfiguraatiomuistiin ja myös käyttäjädataan. Nämä virheet tunnetaan nimellä bit-flip ja ne voivat aiheuttaa konfiguraation muutoksia ja jopa pysyviä vaurioita. On olemassa erilaisia suunnittelutekniikoita, joita voidaan käyttää torjumaan näitä virheitä. Tässä työssä nämä metodit on esitelty ja niitä on hyödynnetty datapolun kehitystyössä. Tämä työ demonstroi miten Flash pohjaiselle FPGAlle kehitetään konfiguraatio, joka laukaistaan matalalle maan kiertoradalle. Konfiguraatio koostuu tieteellisestä datapolusta hiukkasten tunnistukseen ja niiden energioiden määrittelyyn. Datapolku kehitettiin PATE instrumentille ja sen toiminta testattiin simulaattoreilla, sekä laboratoriossa.
Keywords: Cubesat, FORESAIL, FPGA, LEO, Radiation tolerance